How to study the impact of sex and gender in medical research: a review of resources. Issue 1 (October 2016) - McGregor, Alyson; Hasnain, Memoona; Sandberg, Kathryn; Morrison, Mary; Berlin, Michelle; Trott, Justina
Abstract There is a growing appreciation by the biomedical community that studying the impact of sex and gender on health, aging, and disease will lead to improvements in human health. Sex- and gender-based comparisons can inform research on disease mechanisms and the development of new therapeutics as well as enhance scientific rigor and reproducibility. This review will assist basic researchers, clinical investigators, as well as epidemiologists, population, and social scientists by providing an annotated bibliography of currently available resource tools on how to consider sex and gender as independent variables in research design and methodology. These resources will assist investigators applying for funding from the National Institutes of Health since all grant applicants will be required (as of January 25, 2016) to address the role of sex as a biological variable in vertebrate animal and human studies.